The Global South’s “Peace” Initiatives on Ukraine: Revisiting Indonesia’s Middle Power Diplomacy during Jokovi’s Late Administration (2022-2024) .......... 177 - Utama, Muhammad Anugrah (Oblicza dyplomacji, 2025)
Since Russia’s full-scale invasion of Ukraine on February 24, 2022, the Global South has been essentialized as a group of countries lukewarm in their reaction towards the invasion and the Western bloc in general. Their attitude is evidenced by multiple abstentions by Global South countries in UN votes. However, rising Global South middle-powers proposed “peace” initiatives, which painted a different picture since they condemned military attacks on Ukraine, yet refused to name and shame Russia or sanction, and isolate it in multilateral fora. The case of Indonesia is interesting since the country was met with international pressure to condemn Russia’s invasion of Ukraine despite little domestic support. Joko Widodo was the first Asian leader to visit Ukraine and meet President Zelenskyy after the invasion. Moreover, Indonesia’s Minister of Defense (now President), Prabowo Subianto, also proposed a peace plan. However, Indonesia’s “peace” initiatives have been heavily criticised by the West as a “peace of surrender,” although they were praised at home due to Indonesia’s consistency with the non-alignment principle and prioritising domestic interests. By analysing high-level visits and “peace” initiatives in the case of Indonesia, which was holding the presidency of G20 in 2022 and ASEAN in 2023, this paper sheds light on the self-perception of a rising Global South middle-power on their role in building alternative norms and values to the West’s isolationist approach to Russia.